Proton‐conducting hydrogel electrolytes with tight contact to binder‐free MXene electrodes for high‐performance thermally chargeable supercapacitor - Zhijian Du; La Li; Guozhen Shen (Carbon Energy)
Abstract Thermally chargeable supercapacitors (TCSCs) have offered exceptional energy‐converting efficiency for absorbing human epidermal heat and generating and storing electrical energy, which then realize continuous power supply to electronic devices, such as sensors and wearable electronic products, in a wide range of practical significance. Here, we proposed a flexible TCSC by attaching binder‐free Ti3C2Tx MXene@PPy electrodes on both ends of the H3PO4@P(AM‐co‐AA‐co‐AYP K+) hydrogel electrolyte, which exhibits a large thermal power of 35.2 mV K−1 at 50% relative humidity and maximum figure of merit of 2.1. The high performances of the fabricated devices can be attributed to the tunable electrical, thermodynamic, thermoelectric, and mechanical properties of the hydrogel electrolyte by adjusting the acid content and the proportion of zwitterionic compound AYP K+ in the hydrogel, and the high photothermal conversion efficiency and electrochemical performance of the electrodes. Moreover, the stable and outstanding thermofvoltage output (∼200 mV) under different time scenarios of the TCSC makes it possible to drive a strain sensor, accomplishing the objectives of a human activity monitor.